An advanced elastoplastic framework accounting for induced plastic anisotropy fully coupled with ductile damage. (1st October 2021) - Paux, J.; Bettaieb, M. Ben; Badreddine, H.; Abed-Meraim, F.; Labergere, C.; Saanouni, K.
Highlights: A rate-independent macroscopic elastoplastic constitutive model fully coupled with ductile damage is developed. The evolution of plastic anisotropy, accounting for both plastic flow and damage evolution, is accurately modelled. Relevant numerical scheme is developed to integrate and implement the proposed constitutive model in ABAQUS FE software. An original identification methodology is proposed to determine the macroscopic mechanical parameters from multiscale simulations. The reliability of the various implementations is assessed through numerical predictions. Abstract: We present in this investigation an advanced phenomenological approach combining the computational efficiency of classical phenomenological plasticity models and the accuracy and high resolution of multiscale crystal plasticity schemes. Within this advanced approach, a new phenomenological constitutive framework has been developed and implemented into ABAQUS/Standard finite element (FE) code. Compared to classical approaches, this framework allows accounting for initial and induced plastic anisotropy, isotropic nonlinear hardening and the full coupling with isotropic ductile damage. Material parameters corresponding to this phenomenological constitutive framework are identified based on multiscale polycrystalline simulations, where the self-consistent scheme is used to ensure the transition between the single crystal and polycrystal scales. The single crystal mechanical behavior is assumed to be elastoplastic (rate-independent), and microscopic material degradation is well-considered by introducing a scalar damage variable at each crystallographic slip system for each individual grain. The evolution of polycrystalline yield surfaces, induced by the evolution of crystallographic texture, is accurately reproduced by the new constitutive modeling, where the anisotropy parameters are assumed to evolve during plastic deformation. Their evolution laws are identified based on multiscale simulations. The different identification procedures are presented and extensively discussed. The robustness and reliability of this advanced model are analyzed through some relevant numerical predictions obtained by applying a combined tensile/shear test.